Natalie’s Case: PTSD Conceptualization based on Schema Theory - Guindon, Marilyn; Malette, Judith (Canadian Journal of Counselling and Psychotherapy, 2013)
This fictional case study explores the various components of the Schema Theory of Young, Klosko, and Weishaar (2005) and its application to the conceptualization of a Post-Traumatic Stress Disorder (PTSD) case study and psychotherapeutic treatment. The strengths and limitations of the theory in the conceptualization and treatment of PTSD are discussed.